Effects of (−)‐MBP, a novel 5‐HT2C agonist and 5‐HT2A/2B antagonist/inverse agonist on brain activity: A phMRI study on awake mice - Preeti K. Sathe; Gargi R. Ramdasi; Kaylie Giammatteo; Harvens Beauzile; Shuyue Wang; Heng Zhang; Praveen Kulkarni; Raymond G. Booth; Craig F. Ferris (Wiley, 2023)
Abstract A novel serotonin ligand (−)‐MBP was developed for the treatment of schizophrenia that has 5‐HT2A/2B antagonist activity together with 5‐HT2C agonist activity. The multi‐functional activity of this novel drug candidate was characterized using pharmacological magnetic resonance imaging. It was hypothesized (−)‐MBP would affect activity in brain areas associated with sensory perception. Adult male mice were given one of three doses of (−)‐MBP (3.0, 10, 18 mg/kg) or vehicle while fully awake during the MRI scanning session and imaged for 15 min post I.P. injection. BOLD functional imaging was used to follow changes in global brain activity. Data for each treatment were registered to a 3D MRI mouse brain atlas providing site‐specific information on 132 different brain areas. There was a dose‐dependent decrease in positive BOLD signal in numerous brain regions, especially thalamus, cerebrum, and limbic cortex. The 3.0 mg/kg dose had the greatest effect on positive BOLD while the 18 mg/kg dose was less effective. Conversely, the 18 mg/kg dose showed the greatest negative BOLD response while the 3.0 mg/kg showed the least. The prominent activation of the thalamus and cerebrum included the neural circuitry associated with Papez circuit of emotional experience. When compared to vehicle, the 3.0 mg dose affected all sensory modalities, for example, olfactory, somatosensory, motor, and auditory except for the visual cortex. These findings show that (−)‐MBP, a ligand with both 5‐HT2A/2B antagonist and 5‐HT2C agonist activities, interacts with thalamocortical circuitry and impacts areas involved in sensory perception.